Climate Change, Religion and Education: Exploring Influence of Faith-Based Leadership on Environmental Sustainability - Aji Mardani, Dede; Siti Masuroh, Imas (EduBase : Journal of Basic Education, 2025)
Objective: This study aims to examine the role of religious leaders in climate change education in Tasikmalaya through an Islamic approach, with a focus on the use of religious teachings to convey environmental messages and their effectiveness in increasing public awareness and participation. Novelty: This study combines religion with environmental education, making Islamic teachings the basis for environmentally friendly behavior, and highlighting unique practices such as metaphorical narratives and environmentally nuanced worship activities, such as "Green Prayer" and tree planting, which are rarely studied in local contexts such as Tasikmalaya. Methods: This study uses a qualitative approach with in-depth interviews with religious leaders in mosques and religious institutions to explore the views, communication strategies, and challenges faced in conveying climate change issues to congregations. Results: The results of the study show that religious leaders have a strategic role in conveying climate change issues persuasively by connecting religious messages about the importance of protecting nature, but face challenges such as institutional limitations, unequal access to information, and limited scientific understanding among some religious leaders. Conclusion: Religious leaders in Tasikmalaya play an important role in climate change education through Islamic values, but its sustainability and impact require strengthening religious educational institutions, increasing climate literacy, real support from various parties, and cross-sector collaboration.